A retrospective study on the treatment of superficial infantile hemangiomas of the head and neck using topical compresses with 0.5% timolol maleate eye drops - Yang, Li; Chen, Feifan; Li, Kunpeng; Chen, Jiajun; Liu, Wenying; Ji, Yi; Xia, Meng; Xie, Jing; Ding, Ke; Zeng, Qiang; Hou, Fang (Frontiers in Pediatrics, 2026)
IntroductionInfantile hemangiomas, the commonest benign vascular tumors of infancy, often cluster on the head and neck where early treatment can avert permanent disfigurement, prompting us to evaluate 0.5% timolol maleate wet compresses as a non-invasive alternative to oral propranolol.MethodsWe conducted a study of 359 consecutive infants treated at Sichuan Provincial People's Hospital between December 2018 and January 2024. Baseline demographics, lesion site and size, age at initial treatment, treatment duration, and follow-up period were recorded. Treatment outcomes were graded as excellent (complete regression), good (≥50% shrinkage), fair (<50% shrinkage), or poor (no change/growth). Eexcellent/good outcomes were defined as a positive therapeutic effect, while fair/poor outcomes were classified as negative therapeutic effect.Results267 infants (74.37%) achieved positive therapeutic effect, with 117 excellent and 150 good, whereas 92 infants (25.63%) achieved negative therapeutic effect including 53 were fair and 39 poor. Treatment outcomes were significantly better when therapy began before 3 months (early age) (U = 9954, Z = − 3.256, P = 0.001) and for lesions ≤3 cm diameter (small size) (U = 2,869.5, Z = − 13.952, P < 0.001), and multivariate analysis confirmed early age (OR = 0.784, P = 0.024) and small size (OR = 0.113, P < 0.001) as independent predictors of positive therapeutic effect. Adverse events were mild: 24 (6.69%) local irritation, 41 (11.42%) transient systemic symptoms. Skin sequelae were observed in 12 (3.34%) cases.DiscussionTopical timolol compresses offer a safe, effective first-line option for superficial head-and-neck infantile hemangiomas, especially when started early and directed at smaller lesions.